Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean - Tavares, Marcos; Mendonça , Joel Braga De Jr. (Zootaxa, 2022)
Forty species of shore and shallow water brachyuran crabs are reported from the remote oceanic Archipelago Trindade and Martin Vaz (TMV), 11 of which were previously known from Trindade Island, 28 are recorded from the Archipelago for the first time, and one is a new species, Epialtus parvulus sp. nov. This brings the total known shore and shallow water decapod fauna of TMV to 99 species. The opportunity is taken here to elaborate on the taxonomy of the species reported from TMV. One new genus, Mecataleptodius, is recognized for two species, Cancer parvulus Fabricius, 1793, its type species, and Cataleptodius olsoni Manning & Chace, 1990, endemic to Ascension Island. The following seven nominal species are synonymized: Acanthonyx dissimulatus Coelho in Coelho & Torres, 1993; A. scutiformis (Dana, 1851a); Dromia gouveai Melo & Campos Junior, 1999; Epialtus portoricensis Rathbun, 1923; Ranilia guinotae Melo & Campos Junior, 1994; R. saldanhai H. Rodrigues da Costa, 1970; and Omalacantha garthi (Lemos de Castro, 1953). TMV is a subset of the western Atlantic crab fauna (23 species or 57.5%), also including 8 (20%) amphi-Atlantic species, 3 (7.5%) amphi-American, 3 (7.5%) endemic, 2 (5%) cosmopolitan, 1 (2.5%) known from both sides of the Atlantic and the Indo-West Pacific. The crab fauna of TMV, Ascension (AS) and Saint Helena (SH) are compared with one another as well as with that of the oceanic islands Fernando de Noronha (FN) and the Rocas Atoll (RA) by means of nonmetric multidimensional scaling (NMDS) applied to a dissimilarity matrix generated by Jaccard’s coefficient. TMV-FN-RA and AS-SH clustered into two distinct groups according to the composition of their crab fauna. The NMDS analysis ranked the species that cause segregation of the crab faunal assemblages among TMV, AS, and SH, while revealing a gradient in species composition between the two groups of islands (TMV-FN-RA and AS-SH) formed by the amphi-Atlantic species. Island isolation, age and size alone do not explain the existing differences in species richness among TMV, AS and SH. The taxonomic composition of the shallow water fauna in these islands is likely to have been determined by several variables that were interwoven differently along their evolutionary history.